A Study on Compensation Management of Sahil International at Panipat: An Investigation into the Compensation Management Practices of Sahil International in Panipat (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Compensation or Reward system plays vital role in a business organization. Since, among four M’s, i.e. Men, Material, Machine and Money, Men has been most important factor. It is impossible to imagine a business process without Men. Land, Labour, Capital and entrepreneur are four major factors of production. Every factor contributes to the process of production/business and expects return from the business process. The labour expects wages from the process. Wage is a monetary payment, which is made by the employer to his employee for the work done or services rendered. It is a monetary compensation for the services rendered. Wages are usually paid in cash at the end of one day; one month etc. Money wage is the monetary compensation paid by the employer to his employee for the services rendered. Such compensation is also called wage or salary or reward given by a Labour plays significant role in bringing about the process of production/business in motion. Compensation is what an employee receives in return for his or her contribution to the organization. Both primary and secondary data have been used for achieving the objective of the study. Descriptive research design has been used in the study.